Study of viscous micropump - Liew, Chin Kiat. (2008)
Several recent papers discuss a novel viscous micro-pump consisting of the fluid flow between two parallel plates, induced by the rotation of a single cylinder that is placed eccentrically along the flow gap. The primary mechanism of the fluid flow here due to the differential viscous shear imparted by the rotation of the cylinder.